BANTAR GEBANG LEADERPRENEURSHIP YOUTH CAMP - Juliantoro, Barlian; Firdausi, Chalida Zia; Saputra, Dimas Agung; Fauzia, Jimny Hilda; Hanif, Muhammad (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
Bantar Gebang is known as the slum areas where landfills and economic conditions of the majority of the people are below the poverty line. As you know, poverty has multiple effects on the community; one of them is the difficulty of obtaining a quality education. Some consequences of this poverty is the teenage mindset Bantar Gebang less visionary, tough economic conditions improved, and a lack of productivity and creativity. The method used to solve this problem is to analyze the real needs of the target communities, field surveys, completed the licensing administration, recruitment of participants, making materials, training and guidance, visit, and evaluation. Results and the achievement of the program is the implementation of the program Youth Camp for three days to form a teenage mindset Bantar Gebang, pekanan training in a few months for monitoring and realization of values in the material leaderpreneurship pekanan mentoring, as well as joint projects of the participants with the formation house studio Flower (Creative Home Society Bantar Gebang) which has activities such as the manufacture of products / works from recycled materials derived from waste from the mountain Bantar Gebang. Some products / works have been sold which will be used to fully benefit the education of children Bantar Gebang own. Some participants also managed dikader so they are ready to contribute and assist program managers in completing a program agenda. The work of the studio Flower House had participated in the exhibition of works at the Faculty of Public Health (FKM) UI, could get coverage of Alif TV, and also had to get a visit from overseas such as Malaysia.